Appending Diverse π‐Extended Acceptors with Tetrathiafulvalene/Dithiafulvalene Donors: Multistate Redox Properties, Radical Ion Generation, and Mid‐IR‐Absorbing Mixed‐Valence States. Issue 8 (8th January 2018) - Keshri, Sudhir Kumar; Asthana, Deepak; Chorol, Sonam; Kumar, Yogendra; Mukhopadhyay, Pritam
Abstract: Three classes of donor–acceptor (D–A) π‐extended chromophores (1 –12 ) were synthesized through a phosphite‐mediated cross‐coupling reaction, in which the anhydride‐ or imide‐based π‐As and number of tetrathiafulvalene (TTF)/dithiafulvalene (DTF) Ds were systematically changed. Large π rings, such as benzoperylene and coronene, were integrated into the TTF/DTF unit, for the first time, to overcome their high insolubility. The anhydride and imide groups in the π acceptors can significantly alter the frontier orbitals and influence the optoelectronic properties. The D moieties allow the formation of radical cations (D .+ ) and the π‐extended A moieties aid the formation of radical anions (A .− ) by oxidation/reduction under ambient conditions. The molecules revealed UV/Vis/near‐IR absorption, fluorescence extending into the near‐IR region, and amphoteric electrochemical properties. Chromophores10 and12 show solvatochromism in a wide range of solvents. The π‐As with anhydride functionality allow easier electron uptake, relative to the imide groups, whereas the increasing number of D TTF/DTF units make them easy to oxidize. Interestingly, the trans ‐TTF‐fused molecules (1, 6, and11 ) exhibited a mixed‐valence state in the mid‐IR region ( ν ˜ =5130–4000 cm −1 ). Moderate electron coupling between the redox centers is inferred to the compounds being of Robin–Day class II. The multistate redox activity along with panchromism and near‐/mid‐IR optical absorption of these systems can be attractive towards advanced switchable materials. Abstract : Fusion of properties : Three classes of donor–acceptor π‐extended chromophores were synthesized, in which the anhydride or imide‐based π‐acceptors (As) and number of tetrathiafulvalene/dithiafulvalene donors (Ds) were systematically changed (see figure). The molecules revealed UV/Vis/near‐IR absorption, fluorescence extending into the near‐IR region, and amphoteric electrochemical properties.